Mucoadhesive Chitosan-Coated PLGA Nanoparticles of Ashwagandha Extract for Colon-Targeted Delivery - Megaravalli Manjunath, Abhilash; Priya, Sneh; Jyothi, Divya (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: Withania somnifera (Ashwagandha) belongs to the Solanaceae family, well known for its phyto-pharmacological properties such as anti-inflammatory, antioxidant, anti-stress, immunomodulatory, and anticancer properties. The study aimed to formulate and evaluate chitosan-coated PLGA nanoparticles of ashwagandha extract. The nanoparticle formulation technique was considered in order to rectify the various constraints associated with ashwagandhas, such as intestinal absorption, burst release of the drug, and bioavailability issues. Materials and Methods: The CS-PLGA NPs were prepared by single-emulsion solvent evaporation method and it was optimized by using the Box-Behnken design in Design-Expert Software to determine the influence of independent variables PLGA, chitosan concentration and sonication time on particle size. PDI and entrapment efficiency. Results: The particle size, PDI, and zeta potential of the optimized formulation were found to be 187.1nm, 0.148, and 31.3mV. Optical microscopy and SEM suggest that the particles were smooth, spherical, and uniform in size. The entrapment efficiency of the optimized formulation was found to be 84.28%. In vitro drug release study suggests that the enteric coating of the CS-PLGA NPs formulation prevented the drug release in SGF and showed sustained drug release than pure ashwagandha and the drug release kinetics followed the Korsmeyer-Peppas model. Furthermore, the CS-PLGA NPs were evaluated for in vitro antioxidant activity over DPPH, and in vitro cytotoxicity assay over CaCo-2 cell lines. The results showed enhanced antioxidant activity than pure ashwagandha and better cytotoxicity over CaCO-2 cells. Conclusion: The studies concluded that CS-PLGA NPs showed sustained drug release for a prolonged period. The formulation showed good antioxidant activity and better efficacy in cancer cells.
Keywords: Ashwagandha; Nanoparticles; Chitosan; PLGA; Anti-cancer activity